The low-cost biosorbents of Mangosteen (Garcinia mangostana Linn) doped magnesium oxide and titanium dioxide beads for eliminating methylene blue dye - Pornsawai Praipipat; Pimploy Ngamsurach; Junjira Noisri; Thanit Aeamsa-ard (South African Journal of Chemical Engineering)
Two methylene blue (MB) dye adsorbents were synthesized from mangosteen peels modified by magnesium oxide and titanium dioxide called mangosteen peel doped magnesium oxide beads (MMB) and mangosteen peel doped titanium dioxide beads (MTB) to examine which material could greater adsorb MB dye. In addition, several techniques of BET, XRD, FESEM-FIB, EDX, and FT-IR were used for their characterizations. Their MB dye removal efficiencies were investigated by batch experiments, desorption experiments, adsorption isotherms, kinetics, and thermodynamic studies. MTB had a higher specific surface area (15.24 m2/g) and smaller pore size (1.69 nm) than MMB. The results of XRD, FESEM-FIB, EDX, and FT-IR demonstrated the successful additions of magnesium oxide and titanium dioxide into MMB and MTB because they found the specific peaks, characteristic structures, elements, and functional groups of magnesium oxide and titanium dioxide in MMB and MTB. Batch experiments showed they had high MB dye removal efficiencies of more than 97 %, and they could reuse more than three cycles. Freundlich and pseudo-second-order kinetic models were good explanations for their adsorption patterns correlated to chemisorption and their mechanisms to be a chemisorption process. In addition, they were an endothermic process since their MB dye adsorptions increased with increasing temperature.